Edaphic influences on tree species composition and community structure in a secondary-lowland dipterocarp forest of Kota Damansara Forest Reserve, Selangor - Hasya Hannani Ruziman,; Asmida Ismail,; Faezah Pardi,; Siti Khairiyah Mohd Hatta, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research was conducted to determine tree species composition and its relationship with edaphic factors at Kota Damansara Forest Reserve (KDFR), Selangor. Ten study plots of 25 m × 20 m each were established randomly covering a total area of 0.5 ha. In each plot, all trees with diameters at breast height (DBH) of 5 cm and above were tagged and measured whilst topsoil samples at 10 cm depths were taken for their physical and chemical properties. A total of 205 trees from 46 species and 22 families were recorded in KDFR. As for species diversity, the forest showed a Shannon-Weiner Diversity Index (H’) of 3.43 and an evenness value of 0.89 which portrays the uniformity of tree species distribution in the study site. The soil analysis in this study demonstrated that KDFR was dominated by sandy clay texture with organic matter content ranging from 3.94% to 14.24% and acidic soil pH of 3.86. Redundancy analysis indicated that Cinnamomum iners, Cratoxylum arborescens, Myristica cinnamomea, and Syzygium grandis were closely related to soil chemical properties such as nutrients of Ca, P, K. Data and information from this study are crucial as a guideline for future ecological research in tropical forest areas.